A Membrane‐Free Redox Flow Battery with Two Immiscible Redox Electrolytes. (19th July 2017) - Navalpotro, Paula; Palma, Jesus; Anderson, Marc; Marcilla, Rebeca
Abstract: Flexible and scalable energy storage solutions are necessary for mitigating fluctuations of renewable energy sources. The main advantage of redox flow batteries is their ability to decouple power and energy. However, they present some limitations including poor performance, short‐lifetimes, and expensive ion‐selective membranes as well as high price, toxicity, and scarcity of vanadium compounds. We report a membrane‐free battery that relies on the immiscibility of redox electrolytes and where vanadium is replaced by organic molecules. We show that the biphasic system formed by one acidic solution and one ionic liquid, both containing quinoyl species, behaves as a reversible battery without any membrane. This proof‐of‐concept of a membrane‐free battery has an open circuit voltage of 1.4 V with a high theoretical energy density of 22.5 Wh L −1, and is able to deliver 90 % of its theoretical capacity while showing excellent long‐term performance (coulombic efficiency of 100 % and energy efficiency of 70 %). Abstract : Ohne Membran : Die Verwendung nichtmischbarer Elektrolyte führte zu einem Batterieprototyp, der gänzlich ohne Membran auszkommt. Die üblicherweise in Redox‐Flow‐Batterien eingesetzten Metallpaare werden außerdem durch organische Moleküle ersetzt. Da in beiden Elektrolyten unterschiedliche Mechanismen ablaufen, konnte das gleiche Molekül für ein symmetrisches Batteriedesign genutzt werden.